The Scientific and Philosophical Meaning of the Concept of ‘Information’. / El significado científico y filosófico del concepto de ‘información’ - Tarasova, Oksana V.; Khalin, Sergey M.; Melnik, Vladimir V.; Ivanov, Alexey G.; Shcherbinin, Michael N. (Utopía y Praxis Latinoamericana)
ABSTRACT In this paper the relationship of philosophy, specific sciences and information from the point of view of their own information specifics is considered. The information is the diversity inherent in one or another (any) thing. In the article, information is understood not in a mathematical sense – as a complete abstraction (abstraction) from the content moments. The philosophical category "information" is designed to take into account the universal signs of diversity inherent in all things, taking into account all without any exceptions of their content. The category "information" in a certain sense coincides with the category "content". RESUMEN En este artículo se considera la relación de la filosofía, las ciencias específicas y la información desde el punto de vista de sus propios datos específicos. La información es la diversidad inherente a una u otra cosa (cualquiera). En el artículo, la información se entiende no en un sentido matemático, como una abstracción completa (abstracción) de los momentos de contenido. La categoría filosófica "información" está diseñada para tener en cuenta los signos universales de diversidad inherentes a todas las cosas, teniendo en cuenta todo sin excepciones de su contenido. La categoría "información" en cierto sentido coincide con la categoría "contenido".